Investigating the impact of breast positioning control on physical treatment parameters in multi-catheter breast brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer; Bert, Christoph (Strahlentherapie und Onkologie, 2023)
Purpose: To assess the effects of a workflow for reproducible patient and breast positioning on implant stability during high-dose-rate multi-catheter breast brachytherapy. Methods: Thirty patients were treated with our new positioning control workflow. Implant stability was evaluated based on a comparison of planning-CTs to control-CTs acquired halfway through the treatment. To assess geometric stability, button–button distance variations as well as Euclidean dwell position deviations were evaluated. The latter were also quantified within various separated regions within the breast to investigate the location-dependency of implant alterations. Furthermore, dosimetric variations to target volume and organs at risk (ribs, skin) as well as isodose volume changes were analyzed. Results were compared to a previously treated cohort of 100 patients. Results: With the introduced workflow, the patient fraction affected by button–button distance variations > 5 mm and by dwell position deviations > 7 mm were reduced from 37% to 10% and from 30% to 6.6%, respectively. Implant stability improved the most in the lateral to medial breast regions. Only small stability enhancements were observed regarding target volume dosimetry, but the stability of organ at risk exposure became substantially higher. D0.2ccm skin dose variations > 12.4% and D0.1ccm rib dose variations > 6.7% were reduced from 11% to 0% and from 16% to 3.3% of all patients, respectively. Conclusion: Breast positioning control improved geometric and dosimetric implant stability for individual patients, and thus enhanced physical plan validity in these cases.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Adaptive brachytherapy; Computed tomography; Implant stability; Treatment quality; Treatment re-planning